Swedish opinion 1985 - Boalt, Gunnar; Ekman, Gunnar; Hultgren, Sten; Stiftelsen för Opinionsanalyser (Stiftelsen för opinionsanalyser, 1985)
This dataset contains information from the sixth survey of the collection of Swedish opinion surveys. In the 1985 survey two questionnaires were used by approximately 850 respondents each, above there were a shortened questionnaire, including questions common for the two other questionnaires, used by another 300 respondents. In all 200 variables can be found in all questionnaires, 145 in two of them and 151 in only one questionnaire. The questionnaires were compiled with regard to the debate occurring in media during the last quarter of 1984. Many of the questions are replications of questions asked in previous surveys, some of the questions are excluded and a number of questions are added. New questions dealt with: child daycare; government support to private enterprises competing with public service; Swedish export of weapons; heart transplant; the 1985 parliamentary election; war risk in Europe; confidence in the Swedish judicial system.

This dataset contains information from the sixth survey of the collection of Swedish opinion surveys. In the 1985 survey two questionnaires were used by approximately 850 respondents each, above there were a shortened questionnaire, including questions common for the two other questionnaires, used by another 300 respondents. In all 200 variables can be found in all questionnaires, 145 in two of them and 151 in only one questionnaire. The questionnaires were compiled with regard to the debate occurring in media during the last quarter of 1984. Many of the questions are replications of questions asked in previous surveys, some of the questions are excluded and a number of questions are added. New questions dealt with: child daycare; government support to private enterprises competing with public service; Swedish export of weapons; heart transplant; the 1985 parliamentary election; war risk in Europe; confidence in the Swedish judicial system.
Svensk opinion 1985
SVOP85
Keywords: INTERNAL POLITICS; INRIKESPOLITIK; Media; Media; Working conditions; Arbetsförhållanden; Political behaviour and attitudes; Politiska beteenden och attityder; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap